Desmoplastic malignant mesothelioma: a review of 17 cases. Issue 4 (April 1992) - Wilson, G E; Hasleton, P S; Chatterjee, A K
Abstract : AIMS: To identify the histological features of desmoplastic mesothelioma, and to determine its incidence and prognosis. METHODS: Two hundred and fifty five cases of malignant mesothelioma were examined over seven years (1982-9) to identify the desmoplastic variant. Sections were cut at 5 microns and stained with haemotoxylin and eosin and with CAM 5.2 (Dakopatts). Asbestos fibre counts were carried out by light microscopy in 14 cases using the potash digestion method. RESULTS: Seventeen cases were identified as desmoplastic mesothelioma giving an incidence of 6.6%. In 11 cases the cell type in more cellular areas was sarcomatous and in six others it was biphasic. The mean survival time from onset of symptoms to death was 5.8 months for the sarcomatous variant and 6.8 months for the biphasic variant. Twelve of 16 patients had had previous occupational exposure to asbestos, ranging from five months to 43 years. The diagnosis of desmoplastic mesothelioma was only accepted if acellular connective tissue comprised 50% or more of the tumour bulk. Also seen was collagen necrosis, anastomosing bands of often hyalinised collagen with a prominent storiform pattern, and where cellular detail was present there were hyperchromatic nuclei. CONCLUSIONS: Desmoplastic mesothelioma is a rare variant of malignant mesothelioma with a storiform collagen pattern, collagen necrosis, bland acellular collagen and focal cytological features of malignancy. Though rare, it is important to recognise this variant and distinguish it from a pleural plaque, nonspecific reactive pleural fibrosis, pleurisy, rheumatoid disease, or, rarely, spindle cell sarcomas.